An Investigation into the Evolution Law of Young’s Modulus of Polyurethane Coatings with Diluent Contents by Microstructure-Based Tests - Chao Xie; Xiaoxu Lin; Qicai Wang; Bentian Yu; Sheng Li (Advances in Materials Science and Engineering)
Recent studies have indicated that the addition of a diluent significantly affect its mechanical properties and performance of a coating, but no works have been reported on the influence of diluent content on the Young’s modulus of a coating, and the evolution law between them is also not clear. To address the deficiency, polyurethane coatings (paint samples) with different diluent contents were prepared. Force-displacement curves and microscan images of the coatings were obtained by atomic force microscopy, and the Young’s modulus of the coatings was calculated on the basis of the indentation method, and positron annihilation lifetime spectroscopy was used to test the microstructure of the coatings. The results reveal that: (i) Young’s modulus of the coating initially increase and then decreases with diluent content increasing; (ii) the free-volume aperture size had a greater effect on Young’s modulus by grey correlation analysis.